Экспериментальные исследования электротермической стойкости металлических элементов летательного аппарата к прямому воздействию тока искусственной молнии. Часть 2: стойкость медных проводов и кабелей - Баранов, М.И.; Кравченко, В.И.; Носенко, М.А. (Електротехніка і електромеханіка, 2011)
Results of electrothermal stability are experimentally obtained for a number of short copper wires and cables specimens of various brands of air-borne electrical circuits under direct separate or joint action of pulse A or continuous C components of artificial lightning current with peak-time parameters rated according to international requirements.